Germinação e desenvolvimento inicial de plântulas de cajueiro anão precoce sob irrigação salina - Sousa, Alan Bernard Oliveira de (2010)
Considering the socio-economic importance of cashew to the Brazilian northeast and the northeastern problems with water scarcity and quality of irrigation water, the objective of this work was set to study the development of dwarf cashew clones at different stages of development under irrigation with saline water. The first experiment was aimed at evaluating the germination and early growth of seedlings of precocious dwarf cashew (clones: CPC 06, BRS 189, BRS 226 and BRS 265) in greenhouse when irrigated with different salt solutions, in order to observe the differences between the respective responses. The treatments were arranged in a 5 x 4 factorial with four replications, referring y to saline solutions with respective salinities corresponding to the electrical conductivities (ECw) 0, 3, 6, 9 and 12 dS m-1, and four cashew clones (CCP 06 , BRS 189, BRS 226 and BRS 265). Thirty days after seedling emergence, the data were collected and analyzed statistically. All emergence variables were influenced by the salinity. The irrigation with saline water resulted in increased levels of Na+ and Cl- in different plant parts, adversely affecting all the variables of the initial growth of the dwarf cashew clones, with the CCP 06 clone showing the highest salinity tolerance among the clones. The second experiment was aimed at evaluating the growth of dwarf cashew clone BRS 189 under irrigation with saline water. The experiment was conducted at the Pacajus Experimental Field of the Embrapa Agroindústria tropical. The BRS 189 seedlings on the CCP 06 clone rootstock, were transplanted to the ground and subjected to the treatments, from the second month onwards. The treatments were arranged in blocks with four replications and four plants per plot, refering to saline solutions corresponding to the electrical conductivities (ECw) 0.8, 3.0, 6.0, 9.0 and 12.0 dS m-1. After five months, the data were obtained, and subjected to statistical analysis. All the development variables and the leaf dry mass (LDM, or MSF) were influenced by salinity. Only perspiration (of the gas exchanges) was affected by salinity. The salinity limit found in this study corresponded to an electrical conductivity of 1.56 dS m-1, to a fall in potential yield of up to 10%